2023
DOI: 10.3389/fmicb.2023.989162
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota alteration of Chinese young male adults with high-status negative cognitive processing bias

Abstract: IntroductionEvidence suggests that negative cognitive processing bias (NCPB) is a significant risk factor for depression. The microbiota–gut–brain axis has been proven to be a contributing factor to cognitive health and disease. However, the connection between microbiota and NCPB remains unknown. This study mainly sought to explore the key microbiota involved in NCPB and the possible pathways through which NCPB affects depressive symptoms.MethodsData in our studies were collected from 735 Chinese young adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(78 reference statements)
2
2
0
Order By: Relevance
“…and Dorea [33] have also been reported to produce SCFA with the function to effectively reduce blood pressure [34,35], which consistent with our MR results that the increased abundance of those gut microbiota were related to the lower risk of HDP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…and Dorea [33] have also been reported to produce SCFA with the function to effectively reduce blood pressure [34,35], which consistent with our MR results that the increased abundance of those gut microbiota were related to the lower risk of HDP.…”
Section: Discussionsupporting
confidence: 90%
“…But our multivariable MR analysis demonstrated that after adjusting T2D, the protective effect remained, which excluding the influence of confounding factors. Meanwhile, Bifidobacterium [ 9 ], Eubacterium ( ruminantium group ) [ 31 ], Tyzzerella3 [ 32 ], and Dorea [ 33 ] have also been reported to produce SCFA with the function to effectively reduce blood pressure [ 34 , 35 ], which consistent with our MR results that the increased abundance of those gut microbiota were related to the lower risk of HDP.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the abundance of Ruminococcaceae was higher in moderate or severe TBI patients compared to controls ( Urban et al., 2020 ). The relative abundance of Ruminococcaceae and Eggerthellaceae was significantly increased in high-status negative cognitive processing bias adults and cognitive dysfunction mice ( Han et al., 2020 ; Xu et al., 2023 ). On the contrary, in this study, FMT increased the relative abundance of Verrucomicrobiota , Akkermansiaceae , and Akkermansia in TBI mice.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant difference in the β-diversity of microbiota in young adults between high and low NCPB groups. Faecalibaculum abundance was shown to be significantly higher in the High-status NCPB treatment group ( Xu H. et al, 2023 ). It agrees with our findings; our study showed that the relative abundance of Bifidobacterium and Faecalibaculum significantly increased after Ziyan green tea intervention.…”
Section: Discussionmentioning
confidence: 99%